Evaluasi Kebijakan Perbandingan Pengadaan Pegawai Non Aparatur Sipil Negara antara Mekanisme Swakelola dan Mekanisme Outsourcing di Puslatbang PKASN Lembaga Administrasi Negara - Muhammad Afif Muttaqin (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2024)
This research is motivated by issues encountered in the implementation of non-civil servant recruitment policies at the Puslatbang PKASN of the National Institute of Public Administration. These issues include the salaries of non-civil servant staff not meeting the regency or municipality minimum wages (UMK) and disciplinary violations due to inadequate work supervision. There are two policy options for recruiting non-civil servants: self-management and outsourcing. Puslatbang PKASN has implemented both mechanisms; however, the benefits of these mechanisms have not yet been analyzed. Therefore, this study aims to evaluate the non-civil servant staff recruitment policy at the PKASN Training Center from an economic perspective by comparing these two recruitment mechanisms. This aligns with one of the objectives of procurement, which is to achieve the best value for money. In this research, the author employs a comparative study using a quantitative method through cost-benefit analysis (CBA). The cost element is assessed based on expenses incurred at each stage of the recruitment process, while the benefit element is evaluated based on the value of the services provided by non-civil servant staff in supporting Non-Tax State Revenue (PNBP) activities at the Puslatbang PKASN. The Net Present Value (NPV) and Internal Rate of Return (IRR) are used as investment appraisal methods to assess the costs and benefits of the recruitment. The conclusion drawn from the study indicates that both self-management and outsourcing mechanisms are viable for continuing the recruitment of non-civil servants. However, when comparing the two, the self-management mechanism is more beneficial and efficient than the outsourcing mechanism